METODE INTEGRATIF PENETAPAN HUKUM ISLAM: Mengimplementasikan Kajian Normatif dan Empiris - Andika, Musa (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2023)
This article examines the integrative method in the study of Islamic law. This integration can be grouped into two: First, it is integrative between all texts related to the problem being discussed or discussed. Second, it is integrative between texts and other sciences related to the problem being discussed. There are two forms, namely the empirical-historical-inductive form and the doctrinal-normative-deductive form. The first form is the process in which the context of a law (Islam) is formed from society (law in actions) and is to be applied and analyzed systematically. While the second form has more to do with the process of choosing, giving meaning, and formulating (Islamic) legal conclusions from sharia texts.